INTEGRATIVE ANALYSIS OF URINARY RETENTION DISORDERS BASED ON LITERATURE DATA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The causes of urinary incontinence are polyetiological. According to an integrative analysis of the literature, it was found that obstetric injuries (22%) abnormal physical activity (27%), estrogenic failure not corrected during postmenopause, as well as the presence of extra-genital diseases in patients accompanied by an increase in abdominal pressure (42%) or the presence of systemic connective tissue dysplasia (27%) are of particular importance listed factors.